Power quality improvement of PV-WPGS based grid interactive microgrid using MSWL-CLMS control - Gupta, Shikha; Verma, Anjeet; Singh, Bhim; Garg, Rachana; Singh, Alka (Energy systems integration, 2020)
The frequent change, unbalanced non-linear load or electric vehicle charging currents are the prominent source of distorted grid currents and poor power quality in a micro-grid (MG). Thus, in this study, the modified shrinkage widely linear complex-valued least mean squares (MSWL-CLMS) algorithm for photovoltaic-wind power generation system (PV-WPGS) based grid-interfaced MG is presented. MSWL-CLMS algorithm has zero attractor term with the special feature of DC-offset rejection capability. MSWL-CLMS method offers a variable step size, which updates the weight vector and thus provides a significant enhancement in convergence speed, improves the steady-state performance and enables the accurate and rapid estimation of fundamental current components for the generation of the reference current. The control approach is multi-objective, which is proficiently working for coordinated power flow, harmonics mitigation, load balancing, and reactive power compensation. Further, the system is capable of working satisfactorily under unbalance and distorted grid voltages since it is costumed with the improved second-order generalised integrator-frequency locked loop filter, which extracts positive sequence components and generates sinusoidal synchronising signals. To validate the efficacy of MG, simulation and experimental results of the developed scale down prototype are demonstrated in detail.